Development in international law : a policy-oriented inquiry - Qerimi, Qerim R. (Studies in intercultural human rights ;, 2012)
The dominant conceptions of development and the right thereto have been confined to narrow, sectoral interpretations focusing on economic matrices and collective entities such as the state or peoples. This book delimits these key notions of the public order of the 21st century in an entirely new fashion. Drawing on fundamental precepts of policy-oriented jurisprudence, this book offers a comprehensive and systematic study and redefinition of development and the right to development guided by the goal of maximum access by all to the processes of shaping and sharing of all things humans value, including, empirically, aspirations to power, wealth, well-being, affection, enlightenment, skills, respect, and rectitude. This new paradigm of development offers fertile ground for legal and policy responses designed to bring about a public order of human dignity in all parts of the planet.